EDUKASI NENEK UNTUK PENGUATAN PERAN DALAM PENCEGAHAN STUNTING - Lidia Hastuti; Ridha Mardiyani; Yenni Lukita; Yuyun Nisaul Khairillah; Tilawati Aprina; Putri Ayu Acik Kusuma (Institut Kesehatan Yarsi Mataram, 2026)
Background: Grandmothers play a crucial role in supporting child growth and development, particularly in family contexts where they are primary caregivers during pregnancy and early childhood. Evidence indicates that although grandmothers significantly influence caregiving practices, their role is often limited by insufficient knowledge regarding balanced nutrition and appropriate infant feeding practices. Limited understanding of stunting, its determinants, and preventive strategies may contribute to suboptimal nutritional practices that increase children’s risk of growth faltering. Objective: This study aimed to enhance grandmothers’ knowledge of nutrition and caregiving practices and to improve their skills in processing local foods into healthy and nutritious meals. Methods: A community-based intervention was conducted using an educational approach combined with a practical cooking class involving 15 participants. Program effectiveness was evaluated through structured observation of cooking-class performance and measurement of knowledge using validated pre-test and post-test instruments. Results: The findings demonstrated a substantial improvement in participants’ knowledge scores, increasing from 64 ± 2.51 before the intervention to 89 ± 6.72 after the intervention, with a mean difference of 25 ± 3.74. Evaluation of the cooking-class activities indicated that participant performance was categorized as very good. Conclusion: The intervention effectively improved grandmothers’ knowledge regarding caregiving practices, exclusive breastfeeding, and infant and toddler nutrition, highlighting the importance of empowering extended family members as key agents in stunting prevention efforts.